The strategic application of elecytolyte balance to minimize heat stress in broilers - Gamba, Juliana Pereira [UNESP] (2015)
Several physiological and metabolic changes are triggered in broilers submitted to high environmental temperatures, resulting in performance losses. Feed formulation manipulation of the dietary electrolyte balance may be applied to reduce the negative impact of heat stress on broiler performance. This experiment was carried out to evaluate the effect of the manipulations of dietary electrolytes by combining changes in the electrolyte (Na++K+–Cl- ) balance (EB) and in the [(K++Cl- )/Na+] ratio (ER) in broiler feeds. In total, 1575 male broilers between 21 and 46 days old were allotted to 15 treatments in a 5x3 factorial arrangement, consisting of five diets with different EB/ER combinations (150/3, 250/2, 250/3, 250/4, and 350/3). Birds were submitted to heat stress at 25 or 35 days old. Live performance, mortality rate, and carcass traits were evaluated. The strategic formulation of diets with different EB and ER improves live performance and minimize the effect of heat stress on broilers. Under thermoneutral conditions, an EB of 250 mEq/kg and an ER of 3 are recommended, whereas under heat stress, and EB of 350 mEq/kg and an ER of 3 should be applied.